2021
DOI: 10.1051/e3sconf/202132506012
|View full text |Cite
|
Sign up to set email alerts
|

Livelihood of street vendors in Yogyakarta amidst the COVID-19 pandemic

Abstract: This study aims to find out the characteristics of street vendors in Yogyakarta City before and during the COVID-19 pandemic, the livelihood strategies performed by the street vendors during the COVID-19 pandemic, and the relationship between street vendors characteristics and their livelihood strategies during the COVID-19 pandemic. The authors used a quantitative method with a total of 83 respondents. The results indicated age characteristics ranging from 19-68 years, the last education completed by the stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
3
0
1
Order By: Relevance
“…This study revealed that due to the COVID-19 Pandemic, informants suffered a decrease in sales. This is the same as the findings of Pitoyo et al (2021), stating that the pandemic reduced income or no income for informal street vendors. According to Shafi et al (2020) and Wegerif (2020), informal street vendors are facing several issues, such as financial, a decrease in demand, and a reduction in sales and profit, which is similar to the findings of this study.…”
Section: "Few Customers […]"-Lizalyn Ferrer 2 "Low Income Sometimes W...supporting
confidence: 84%
See 2 more Smart Citations
“…This study revealed that due to the COVID-19 Pandemic, informants suffered a decrease in sales. This is the same as the findings of Pitoyo et al (2021), stating that the pandemic reduced income or no income for informal street vendors. According to Shafi et al (2020) and Wegerif (2020), informal street vendors are facing several issues, such as financial, a decrease in demand, and a reduction in sales and profit, which is similar to the findings of this study.…”
Section: "Few Customers […]"-Lizalyn Ferrer 2 "Low Income Sometimes W...supporting
confidence: 84%
“…That's why countries all over the world decided to implement drastic measures to fight the effects of a pandemic. The immediate strategy is to limit transmission and minimize the harm of the pandemic (Pitoyo et al, 2021). The informal street vendors have no other choice but to adhere to the policies and safety protocols stated by the authorities to avoid encountering problems in their operations and for their safety as well as negating the study of Thulare & Moyo (2021) stating that the mounting pressure of not being able to provide for their family's needs pushed informal street traders to continue their operations disregarding the safety regulations.…”
Section: Theme 2 Policy Adherencementioning
confidence: 99%
See 1 more Smart Citation
“…Indonesia adalah negara yang kaya akan sumber daya alam nabati sebagai sumber karbohidrat dan serat pangan, misalnya umbi suweg dan umbi garut. Umbi suweg mengandung karbohidrat yang relatif tinggi yaitu 80%-85% dan memiliki komponen protein, lemak, vitamin, dan mineral [3]. Umbi suweg juga dapat dipakai sebagai pangan fungsional yang bermanfaat untuk menekan peningkatan kadar glukosa dalam darah, sekaligus mengurangi kadar kolesterol serum darah, karena suweg memiliki indeks glikemik rendah, kandungan serat pangan yang tinggi, dan memiliki sifat fungsional hipoglikemik dan hipolipidemik.…”
Section: Pendahuluanunclassified
“…MSMEs in less developed countries, where informal businesses are prevalent, often struggle to overcome unwanted situations due to resource constraints and dependence on the local market. Additionally, limited government support could hinder the accelerated recovery of affected businesses [15,16].…”
Section: M5mentioning
confidence: 99%